El ambiente de seleccion, lugar, epoca de siembra, inoculacion, fertilidad: la importancia de escoger el ambiente a reflejar las caracteristicas varietales buscadas en el programa de seleccion - Díaz, O. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
Identifying adequate environmental conditions (alt., temp., RH) is recommended for var. selection. The exptl. site for adaptation and yield nurseries must be a representative bean producing area, with high-or low-fertility soils, where constraints persist systematically. Planting time should also be consistent with the objective of the breeding program, either for yield or for disease and pest resistance. (CIAT)